Audit partner rotation, and its impact on audit quality: Evidence from India - Partha Mohapatra; D. Ajit; Sudershan Kuntluru; Athira A (Cogent Economics & Finance, 2021)
Using multiple indicators of audit quality, the study examines the impact of audit partner rotation on audit quality in India based on 1,694 firm years for the period of 2011-2017 when the institutional set up for audit partner rotation was voluntary. The empirical results indicate that the audit partner rotation had no significant impact on audit quality as measured by discretionary accruals and going concern audit opinion. The study finds that other factors like loss year, size of the firm, value, leverage have a statistically significant impact on audit quality. The empirical results also indicate an inverse relationship between audit fees and audit partner rotation implying, price-cutting of the audit. The findings are important to regulators regarding the significance of audit partner rotation in enhancing audit quality.
Keywords: H83; M42; M48; 330; audit costs; Audit partner rotation; Audit quality; discretionary accruals; going concern audit opinion; India